The concept of experience and the sociology for women - Kohoutková, Jitka (2006)
The topic of the thesis The Concept of Experience and the Sociology for Women is feminist sociology. The theoretical background for the thesis draws on feminist theories utilizing the concept of womens experience standpoint theories, feminist critique of knowledge and feminist project of sociology for women. The goal of the thesis is to arrive at and present the critical feminist sociology. The thesis outlines the history of the concept of womens experience in the feminist debates and theories as well as feminist debate about the masculine nature of science and knowledge. With the use of both theoretical approaches the thesis concludes with introducing the project of sociology for women in which the concept of womens experience is acknowledged as the starting position and perspective for any sociological inquiry. Embracing the feminist claim for stronger reflexivity and situated knowledges allowed the author going beyond the sociology for women and present feminist critical sociology.